Isolation, Biochemical Characterization, Antibiogram Pattern and PCR Based Confirmation of Brucella from Cows and Buffaloes - Patel, Ritesh N.; Roy, Ashish; Bhanderi, Bharat B; Vagheshwari, Dhaval H (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Brucellosis is a worldwide zoonotic disease that still constitutes a major public health problem in India. In the current study, Brucella were  isolated from aborted samples and typed by both molecular and conventional techniques. A total 114 aborted samples were collected  from cows and buffaloes in and around Anand district. Aborted samples were cultured on the Brucella agar medium and incubated for  24–48 h. Three samples from cow were found to be positive for Brucella. All the isolates were positive for catalase, oxidase and nitrate  reduction while negative for urease reaction, indole test, VP test, motility examination and production of H2S. For the detection of  Brucella DNA by PCR, three different genus-specific primer pairs viz., B4/B5, JPF/JPR, and F4/R2 were used. All three Brucella isolates  were positive by B4/B5 and F4/R2, while two isolates were positive for JPF/JPR. For species-level identification of Brucella isolates were  subjected to AMOS PCR and Bruce-ladder PCR, and were found to be B. abortus.
Keywords: AMOS-PCR; Brucella; Buffalo; Bruce-ladder; Cattle; PCR